(untitled) (World Bulletin of Public Health, 2022)
Diagnosis and treatment of pleural empyema remains an urgent problem in surgery. With the advent of multispiral computed tomography, the possibilities of diagnosing pathology of the chest and pleura organs have increased. The data of examination and treatment of 36 patients with pleural empyema of various etiologies who were treated in the purulent surgical department of the clinical base of the Bukhara State Institute in 2012-2021